Contrasting Effects of Finding Meaning and Searching for Meaning, and Political Orientation and Religiosity, on Feelings and Behaviors During the COVID-19 Pandemic. (June 2022) - Newman, David B.; Schneider, Stefan; Stone, Arthur A.
Perceiving life as meaningful can buffer against negative experiences, whereas searching for meaning in life is often associated with negative outcomes. We examined how these individual differences, along with religiosity and political orientation, are associated with feelings and health-related behaviors during the COVID-19 pandemic ( N = 7, 220; U.S. nationally representative sample). Conservatism and religiosity predicted less negative effect; conservatives (but not the highly religious) were less likely to engage in preventive actions such as wearing face masks and social distancing. Controlling for political orientation, religiosity, and demographics, the presence of meaning in life predicted less negative affect and greater healthy preventive actions, whereas searching for meaning predicted greater negative affect and more preventive and risky health behaviors. Thus, the perception that life is meaningful not only predicts an individual's emotional well-being but is also associated with beneficial actions that can help protect others from the spread of the coronavirus.